Ameliorating epistemic injustice in practice: Communication strategies in a research project with refugee youth coresearchers - Elin Inge; Anna Pérez‐Aronsson; Kalid Ibrahim; Reem Aljeshy; Anna Sarkadi; Georgina Warner (Health Expectations)
Abstract Introduction Many researchers want to include seldom involved groups, such as refugees and youth, in patient and public involvement (PPI), but experience a number of barriers. The PPI research community calls for critical evaluations that are prospective, data‐based and conducted by researchers and public contributors together. In this study, we conducted a longitudinal evaluation of a core activity in all collaborations: communication strategies. The aim was to evaluate the communication strategies adopted throughout a research project with refugee youth coresearchers. Methods This article is based on the evaluation of a project where refugee youth were involved in the online adaptation of a group‐based programme for youth with posttraumatic stress. Behavioural observations and field notes collected during the project were analysed with qualitative content analysis and a readability index, and discussed through the lens of epistemic injustice. The article was cowritten by researchers and refugee youth. Findings Four manifest categories were identified: Facilitating engagement through coplanning and circumstantial flexibility; Different needs require different channels; It's not just about the channel—facilitation skills matter; Finding a common language opens a communicative flow. In addition, a latent underlying theme reflecting the role of trust was identified: Interactive moments facilitate trust—trust facilitates richer involvement. Conclusion At the core of the identified communication strategies were strengthening relationship‐building and actively facilitating involvement. Establishing trusting relationships enabled refugee youth to share input. The communication strategies increased hermeneutical justice by contributing to a common understanding; thus, taking a step towards ameliorating epistemic injustice. Patient or Public Contribution This article is a participatory analysis of a PPI process; it was written in collaboration between researchers and refugee youth coauthors, who were all previously involved in the evaluated project.